Composition and spore abundance of arbuscular mycorrhizal fungi in sweet potato producing areas in Uganda - Mukhongo, Ruth Wilhem; Ebanyat, Peter; Masso, Cargele; Tumuhairwe, John Baptist (Frontiers in Soil Science, 2023)
Introduction Farming systems influence composition and abundance of microbial communities. Methodology A study was conducted using morphotyping and enumeration methods to determine the composition and spore abundance of Arbuscular Mycorrhizal Fungi (AMF) in sweet potato producing regions in eastern Uganda. Sampling was done from fields with crop types (CTs) including legumes (groundnuts, common beans, cowpea, soybeans, green grams), sorghum, sweet potato, and fallowed fields which were used as a control. Three agro-ecological zones (AEZs) i.e., Mt. Elgon High Farmlands (MEHF), Lake Victoria Crescent (LVC), and Southern and Eastern Lake Kyoga Basin (SELKB) were considered. Results and discussion A total of 6 AMF genera comprising of Glomus, Acaulospora, Scutellospora, Entrophospora, Archaeospora, and Gigaspora were isolated from the study sites. Agro-ecological zones had a significant (p<0.05) effect on Entrophospora spp. while crop types had a significant (p<0.05) effect on Gigaspora spp. although all the AMF genera were present in all AEZs and CTs. Spore abundance was similar across the AEZs except for MEHF (177) which was lower while spore abundance lowest in sweet potato (177) and largest in fallow (224), attributed to soil properties and similar crops included in the crop rotation program. The AMF can be isolated, identified, and multiplied to produce bioinoculants for the regions.